Search for squarks and gluinos with the ATLAS detector in final states with jets and missing transverse momentum using 4.7 fb⁻¹ of √s = 7 TeV proton-proton collision data - Alonso, Francisco (2013)
A search for squarks and gluinos in final states containing jets, missing transverse momentum and no high-pT electrons or muons is presented. The data represent the complete sample recorded in 2011 by the ATLAS experiment in 7 TeV proton-proton collisions at the Large Hadron Collider, with a total integrated luminosity of 4.7 fb⁻¹. . No excess above the Standard Model background expectation is observed. Gluino masses below 860 GeV and squark masses below 1320 GeV are excluded at the 95% confidence level in simplified models containing only squarks of the first two generations, a gluino octet and a massless neutralino, for squark or gluino masses below 2 TeV, respectively. Squarks and gluinos with equal masses below 1410 GeV are excluded. In minimal supergravity/constrained minimal supersymmetric Standard Model models with tanβ= 10, A₀ = 0, and = μ > 0, squarks and gluinos of equal mass are excluded for masses below 1360 GeV. Constraints are also placed on the parameter space of supersymmetric models with compressed spectra. These limits considerably extend the region of supersymmetric parameter space excluded by previous measurements with the ATLAS detector.